2014
DOI: 10.1177/070674371405901205
|View full text |Cite
|
Sign up to set email alerts
|

Neurocognitive Functioning in Overweight and Obese Patients with Bipolar Disorder: Data from the Systematic Treatment Optimization Program for Early Mania (STOP-EM)

Abstract: Objective: Obesity is frequent in people with bipolar I disorder (BD I) and has a major impact on the course of the illness. Although obesity negatively influences cognitive function in patients with BD, its impact in the early phase of the disorder is unknown. We investigated the impact of overweight and obesity on cognitive functioning in clinically stable patients with BD recently recovered from their first manic episode. Method: Sixty-five patients with BD (25 overweight or obese and 40 normal weight) rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 66 publications
0
11
0
Order By: Relevance
“…11 In addition to its adverse physical health correlates, obesity has been associated with a more pernicious course of BD in adults, including increased frequency of mood episodes, increased treatment resistance, poor cognitive function and increased suicidality. 2,[12][13][14] Similar to findings in adults with BD, overweight/obesity in adolescents with BD has been associated with greater prevalence of substance use disorder, self-injurious behaviour, suicidality, neurocognitive dysfunction and greater number of psychiatric hospital admissions. 2,6,15,16 Recent general population data from the United States indicated that although overweight/ obesity was not more common among adolescents with BD than in other adolescents, in this largely untreated sample it was nonetheless associated with indicators of BD severity, such as suicide attempts and psychiatric hospital admission.…”
Section: Introductionmentioning
confidence: 59%
“…11 In addition to its adverse physical health correlates, obesity has been associated with a more pernicious course of BD in adults, including increased frequency of mood episodes, increased treatment resistance, poor cognitive function and increased suicidality. 2,[12][13][14] Similar to findings in adults with BD, overweight/obesity in adolescents with BD has been associated with greater prevalence of substance use disorder, self-injurious behaviour, suicidality, neurocognitive dysfunction and greater number of psychiatric hospital admissions. 2,6,15,16 Recent general population data from the United States indicated that although overweight/ obesity was not more common among adolescents with BD than in other adolescents, in this largely untreated sample it was nonetheless associated with indicators of BD severity, such as suicide attempts and psychiatric hospital admission.…”
Section: Introductionmentioning
confidence: 59%
“…In a study evaluating neurocognitive functions in overweight and obese bipolar patients, there was a weak negative correlation between BMI and nonverbal memory, and no correlation between BMI and other cognitive domains. 39 Another study showed a correlation between hypertension and global cognitive dysfunction in remitted BD. 40 The negative correlation between waist circumference and participation in social activities can be explained by the fact that people with abdominal obesity refrain from participating in social activities due to social attitudes toward obese bodies, but further studies are needed in this regard.…”
Section: Discussionmentioning
confidence: 99%
“…CVRFs are also associated with reduced neurocognitive function, particularly in frontal‐executive tasks 49‐57 . The strength of this association may depend in part on the symptomatic status and on the illness duration/stage 58,59 . Prospective studies indicate that the association among CVRFs, particularly obesity, and impaired cognition is bidirectional 53,59 .…”
Section: Traditional Cardiovascular Risk Factorsmentioning
confidence: 99%